Influência do ano eleitoral, do mandato eleitoral e da mudança de Gestor Público sobre as mudanças na composição dos gastos públicos: um estudo nos municípios brasileiros - Morais, Lívia Maria Freire de (2018)
Based on the literature on political-budget cycles, the present research aims to verify the influence of the electoral year, the electoral mandate and the change of public manager on the changes in the composition of the public expenses of the Brazilian municipalities. To achieve this objective, the dependent variable consisted of an index (IMCGP) that reflects changes in the composition of public expenditures, which is compounded by the combination of changes in public expenditures classified according to four natures of expenditure: personnel and social charges, others current expenses, investments and financial inversions. The sample was composed of 4,069 Brazilian municipalities from 2005 to 2016, comprising three electoral cycles. We used the regression technique with panel data, since the sample is composed of sectional and temporal data. Evidence has shown that the election year exerts a negative influence on IMCGP. On the other hand, the electoral mandate and the change of mayors influence positively on the IMCGP of the municipalities. In this sense, the research concludes that the first electoral mandate and the alternation of mayors of the municipalities consist of political factors that impel the realization of greater changes in the composition of the expenses on the part of the governors. Regarding the years in office, it was observed that the greatest changes in the composition of expenditures did not occur in the electoral year, but in the first year of the electoral mandate, driven mainly by the changes of mayors typical of the first year of the mandate.